Research skills in nursing undergraduate students: A case study at a Chilean private university - Vera, Fernando (Open Science Journal, 2020)
Tertiary education in Chile has increased radically over the past 20 years. According to the Higher Education Information Service (Servicio de Información de Educación Superior: SIES), in 2018, there were 1,188,423 students enrolled in undergraduate programs, totaling 94.1% of the 1,262,771 students enrolled in Higher Education Institutions (SIES, 2018). In fact, there are both private and public universities available for students who seek an undergraduate program. In this context, nursing is an increasingly in-demand program and an option for all ages in this country. In general, this program calls for and develops skills and qualities essential to the Nursing profession, amongst them: technical knowledge, critical thinking, empathy and strong communication skills. The purpose of this paper is to examine the main difficulties that undergraduate nursing students, at a Chilean private university, encounter when conducting their research proposal. Two instruments were used to collect data: an online self-administered questionnaire consisting of 14 closed-ended questions and a rubric to assess students’ research proposals. The sample comprised of a total of 41 students, who were in the 23-52 age group. The average age was 34 years (SD= 5.78). Female students accounted for 88.5% of the total group. Findings indicate that there is a gap in research skills in these students. This article is based on the author’s teaching experience.